BOOSTING VOCABULARY OUTPUT FOR BEGINNER WITH EDUCAPLAY APP AND PBL - Nur Ainun Arsyad; Rafi’ah Nur; Salasiah Ammade; Ammang Latifa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Beginners in English face multiple obstacles in their language learning journey. One of the most significant challenges is building a sufficient vocabulary base, which is crucial for comprehension and communication. This research investigates the effect of integrating the Educaplay application with Problem-Based Learning (PBL) to enhance vocabulary output in beginner-level English learners. Conducted at SD Muhammadiyah 3 Parepare with a pre-experimental design (one-group pretest-posttest), the study involved 16 fourth-grade students. Students were given vocabulary instruction through six sessions of Educaplay-based PBL. Findings showed a significant increase in vocabulary output, with the mean score improving from 61.56 (pretest) to 84.69 (posttest). The t-test value (1.91) exceeded the t-table value (1.75), indicating a statistically significant difference. Students also demonstrated a 93% average level of interest based on questionnaire results. . the findings robustly support the effectiveness of integrating the Educaplay application within a Problem-Based Learning model for beginner English students, yielding significant improvements in vocabulary acquisition and fostering a very high level of learning interest This study confirms that Educaplay, when implemented within the PBL framework, effectively enhances vocabulary acquisition and student engagement in English for beginners.